FORMULASI MASKER CLAY EKSTRAK METANOL DAUN JARONG (Achyranthes aspera L.) dan UJI AKTIVITAS ANTIOKSIDAN DENGAN METODE DPPH - Kristantri, Rika Sebtiana (Parapemikir : Jurnal Ilmiah Farmasi, 2024)
Skin needs antioxidant compounds to overcome oxidative damage caused by free radicals due to UV radiation. One of them is using cosmetics formulated with antioxidants. Jarong leaves contain various phytochemical compounds, one of which is flavonoids, which have the potential to act as antioxidants with their ability to ward off free radicals. Jarong leaves as an antioxidant will be more effective and acceptable if formulated in topical preparations such as clay masks. This research aims to determine the effect of bentonite and kaolin concentrations on physical characteristics and determine antioxidant activity methanol extract of jarong leaf in clay mask using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Clay mask formulation with bentonite 2.122% and kaolin 38.878% the extract concentration used was 0.30%. The response parameters of antioxidant activity which are expressed by the IC50 value. The research results show that methanol extract of jarong leaf can inhibit free radicals with an IC50 value 46,4454 ppm which is included in the category of very strong antioxidant